2020
DOI: 10.1111/1751-7915.13647
|View full text |Cite
|
Sign up to set email alerts
|

Comparative secretome of white‐rot fungi reveals co‐regulated carbohydrate‐active enzymes associated with selective ligninolysis of ramie stalks

Abstract: In the present research, Phanerochaete chrysosporium and Irpex Lacteus simultaneously degraded lignin and cellulose in ramie stalks, whereas Pleurotus ostreatus and Pleurotus eryngii could depolymerize lignin but little cellulose. Comparative proteomic analysis of these four white-rot fungi was used to investigate the molecular mechanism of this selective ligninolysis. 292 proteins, including CAZymes, sugar transporters, cytochrome P450, proteases, phosphatases and proteins with other function, were successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Due to challenges in protein separation, this approach only identified dozens of proteins per sample ( Abbas et al., 2005 ; Ravalason et al., 2008 ; Salvachúa et al., 2013a ; Vasina et al., 2016 ; Xiao et al., 2017 , 2019 ; Zorn et al., 2005 ). The utilization of liquid chromatography-tandem mass spectrometry (LC-MS/MS) for shotgun or bottom-up proteomic studies – which aim to identify proteins from the overall pool of peptides in one sample – as well as the recent release of many WRF genomes, has increased the throughput of proteomic analyses and expanded the number of identified proteins to hundreds per sample ( del Cerro et al., 2021 ; Fernández-Fueyo et al., 2012 ; Fernández-Fueyo et al., 2016 ; Floudas et al., 2012 ; Miyauchi et al., 2020a ; Miyauchi et al., 2017 ; Xie et al., 2021 ). Other modern proteomic approaches include quantitative and top-down proteomics – which provide additional information on exact protein abundances and post-translational modifications, respectively ( Toby et al., 2016 ) – and will further expand the breadth of proteomic research in WRF ( Alfaro et al., 2014 ).…”
Section: Spatiotemporal Metabolism Of Wrf From a Proteomics Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…Due to challenges in protein separation, this approach only identified dozens of proteins per sample ( Abbas et al., 2005 ; Ravalason et al., 2008 ; Salvachúa et al., 2013a ; Vasina et al., 2016 ; Xiao et al., 2017 , 2019 ; Zorn et al., 2005 ). The utilization of liquid chromatography-tandem mass spectrometry (LC-MS/MS) for shotgun or bottom-up proteomic studies – which aim to identify proteins from the overall pool of peptides in one sample – as well as the recent release of many WRF genomes, has increased the throughput of proteomic analyses and expanded the number of identified proteins to hundreds per sample ( del Cerro et al., 2021 ; Fernández-Fueyo et al., 2012 ; Fernández-Fueyo et al., 2016 ; Floudas et al., 2012 ; Miyauchi et al., 2020a ; Miyauchi et al., 2017 ; Xie et al., 2021 ). Other modern proteomic approaches include quantitative and top-down proteomics – which provide additional information on exact protein abundances and post-translational modifications, respectively ( Toby et al., 2016 ) – and will further expand the breadth of proteomic research in WRF ( Alfaro et al., 2014 ).…”
Section: Spatiotemporal Metabolism Of Wrf From a Proteomics Perspectivementioning
confidence: 99%
“…However, comparative analysis of a diversity of WRF secretomes within the same study is a powerful approach to avoid experimental and technical variability and establish direct correlations among organisms and/or cultivations conditions. For instance, Xie et al. (2021) showed a correlation between WRF species and lignocellulose degradation patterns and showed that two selective lignin-degrading WRF, P. ostreatus and Pleurotus eryngii , secrete higher abundances of ligninolytic and lower abundances of cellulolytic enzymes compared to P. chrysosporium and I. lacteus, WRF that simultaneously degrade lignocellulose, in ramie stalks-containing cultivations.…”
Section: Spatiotemporal Metabolism Of Wrf From a Proteomics Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…The phloem of ramie is accounted for only about 15% of its biomass, and the stalks reach to more than 60% (Meng et al 2018 ). Ramie stalks composed of 44% cellulose, 31% hemicellulose and 18.1% lignin, making it a suitable substrate for biofuel production (Xie et al 2021 ). However, the lignin content of native lignocellulosic biomass is highly resistant to cellulase degradation for cellulose, resulting in low cellulose conversion (Guo et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%